Spike count and morphology in the classification of epileptiform discharges - Aanestad, Eivind; Gilhus, Nils Erik; Olberg, Henning Kristian; Kural, Mustafa Aykut; Beniczky, Sándor; Brogger, Jan (Frontiers in Neurology, 2023)
Purpose: To investigate the impact of Bergen Epileptiform Morphology Score (BEMS) and interictal epileptiform discharge (IED) candidate count in EEG classification. Methods: We included 400 consecutive patients with focal sharp discharges in their EEG, but no previously diagnosed epilepsy from a clinical SCORE EEG database during 2013-2017. Three blinded EEG-readers marked all IED candidates. BEMS and IED candidate count were combined to classify EEGs as epileptiform or non-epileptiform. Diagnostic performance was assessed and then validated in an external dataset. Results: IED candidate count and BEMS were moderately correlated. The optimal criteria to classify an EEG as epileptiform were either one spike at BEMS >=58, two at >=47, or seven at >=36. These criteria had almost perfect inter-rater reliability (Gwet’s AC1 0.96), reasonable sensitivity 56-64%, and high specificity 98-99%. The sensitivity was 27-37% and the specificity 93-97% for a follow-up diagnosis of epilepsy. In the external dataset, the sensitivity for an epileptiform EEG was 60-70% and the specificity 90-93%. Conclusion: Quantified EEG spike morphology (BEMS) and IED candidate count can be combined to classify an EEG as epileptiform with high reliability, but with lower sensitivity than regular visual EEG review.